Reputation in the age of disruption: A case study of PT Pos Indonesia - Aditya, Mario Osann; Erwina, Wina; Priyatna, Centurion Chandratama (PRofesi Humas, 2023)
Background: The age of disruption is inevitable nowadays, forcing companies to adapt to the current challenges and situations to stay relevant. PT Pos Indonesia is one of the companies experiencing negative impacts, resulting in decreased work performance, corporate stability, and even corporate reputation. Therefore, PT Pos Indonesia must swiftly retake the market narrative and improve its reputation. Purpose: The present study aimed to analyze the need of PT Pos Indonesia to bring back its reputation in the age of disruption. Methods: It is a qualitative and explorative case study. In-depth interviews, participatory observations, and document analysis collected data. Results: Pos Indonesia’s efforts to be able to move more quickly and precisely is a good step, with three primary reasons, namely to increase profitability, maintain stability, and show good growth prospects for the company. Other elements also accompany these three fundamental reasons due to observations made by Pos Indonesia. Conclusion: The company needs to consistently observe emerging gaps because it will significantly help Pos Indonesia stay relevant. In addition, consistency will also keep Pos Indonesia moving on track with corporate innovation, allowing it to improve the company’s presence and reputation in a shorter amount of time. Implication: Consistency is needed to increase profitability, maintain stability and show good growth prospects. If done consistently and optimally, this will keep Pos Indonesia moving in the corridor of corporate innovation and enable reputation improvement.